Congenital heart disease in children and adultsOutcomes of long-term endocavitary cardiac pacing in children - Szklarz, Eliza; Jędrzejczyk-Patej, Ewa; Czapla, Krystyna (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
Background: The development of neonatal cardiology and cardiac surgery, as well as the earlier diagnosis of congenital defects, arrhythmias, and cardiac conduction disorders, contributed to the systematic increase of the number of children and young adults undergoing electrophysiological procedures, as well as to the reduction of the age at which these procedures are performed. Children requiring permanent cardiac pacing constitute 1-2% of the entire population qualified for cardiac pacemaker implantation. The aim of this study was to present the results of permanent pacing therapy employed in children undergoing endocavitary pacemaker implantation in long-term follow-up. Material and methods : The study group included 106 children up to 12 years after pacemaker implantation. The age range of the children was 2-17 years, while their weight was between 13 and 58.8 kg. The group included 91 children after surgical repair of congenital heart defects, 7 patients with congenital complete atrioventricular block, 4 patients with postinflammatory sinus node dysfunction, and 4 patients with symptomatic bradycardia after heart transplantation. Results: All 106 patients were implanted with endocardial system types consistent with their indications for pacing. The mean duration of the procedure was 92 min, while the average duration of fluoroscopy was 9 min 37 s. The average battery lifespan in follow-up was 5 years. Conclusions: Transvenous pacemaker implantation in children is a minimally invasive method, feasible for use even in small children.